Influence of Some Agricultural Extension Television Elements on Diffusion of Agricultural Information, Rural Knowledge and New Technologies to Tenants in the Gezira Province - M. Abdel Rahman, Ahmed; A. Elhado, Mohamed (المجلة الزراعية; مجلد 3 عدد 1 (2005), 2021)
Agricultural extension and rural information services provide rural people with information and rural knowledge which they need in order to increase their production, incomes and consequently improve their standard of living. Therefore, rural information systems must involve rural communities and local needs must also be of prime importance. Field surveys were used to collect data from 120 tenants in the Gezira Province in 2003/2004 growing season selected from a total population of 120000 tenants distributed in eight extension areas in the province by using the simple random sampling technique. The collected data were statistically analyzed using percentage and frequency distributions. The results showed unsuitability of some elements of extension television with tenants conditions and preferences in the Gezira Province. It could be concluded that the inconvenient time of broadcasting of extension television programs and their improper presentation negatively influenced diffusion of agricultural information, rural knowledge and new technologies to tenants in the Gezira Province. Thus, more attention should be given to planning, producing and time of transmitting of extension message through effective use of extension television elements.